Co-operation in Collection Development : Summary of the Meeting of the Division of Collection Development, Prague, July 1999 - Wade, Ann (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
Bernard Naylor gave a summary of some important milestones leading up to the present situation in library co-operation in the UK. From 1979 to 1986 three reports from the UK Library and Information Services Council on the future development of libraries had been published. The reports had argued for a cross sectoral approach to any attempts at co-operation, for a regional focus, and for local information plans. The reports also emphasized that all planning involved participation both from the top/down and from the bottom/up. All reports had made clear that only limited funds would be available for future planning.